Penguatan Kapabilitas Internal Berbasis Inovasi dan Kompetensi SDM untuk Pencapaian Maturity Rating BLU - Toyibah, Afnani (Jurnal Pendidikan Kesehatan (e-Journal), 2025)
This study aims to examine efforts to enhance internal capabilities through innovation and employee participation at the Public Service Agency (BLU) of the Politeknik Kesehatan, Ministry of Health (PKM) Malang. A qualitative approach was employed, with data obtained through in-depth interviews with several informants from different work units. The findings reveal that BLU PKM management demonstrates a high level of openness in accepting creative ideas from employees, thereby fostering a conducive participatory climate. Institutional support for human resource (HR) capacity development is evident through the facilitation of training, seminars, and the acceptance of innovative ideas, many of which originate from staff-level employees. The mechanism for submitting ideas is flexible, allowing both informal and formal channels, and students are also involved as stakeholders through discussion forums. Decentralization of authority at the department and study program levels further strengthens the organization’s responsiveness to innovation. Overall, the enhancement of internal capabilities at BLU PKM has progressed well through managerial openness, active employee participation, and HR development support, although further reinforcement in digitalization is needed to ensure more sustainable innovation